Managerial Decisions in the Process of Ukrainian State-Building - MELNICHUK, L. V.; KRYVOSHEYEVA, Ye. A. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article explores the essence and significance of managerial decisions in the process of Ukrainian state-building. It identifies the main historical stages of the formation of the national system of governance and highlights the evolution of managerial institutions in the context of political, economic, and social transformations. Particular attention is paid to the influence of decentralization, digital transformation, and European integration on the quality and transparency of decision-making processes. The research substantiates the need to enhance institutional capacity, professional competence, and data-based analytical approaches to ensure the effectiveness of public administration. The author emphasizes that managerial decisions in Ukraine should combine scientific reasoning, strategic foresight, and civic participation to strengthen democratic governance and sustainable development. The study concludes that improving the decision-making system is a key factor in advancing Ukrainian statehood and its resilience to internal and external challenges.